Histology of metastatic colorectal cancer in a lymph node - Shozo Yokoyama; Takashi Watanabe; Yoichi Fujita; Shuichi Matsumura; Katsuya Ueda; Shotaro Nagano; Ikuharu Kinoshita; Daisuke Murakami; Hirotaka Tabata; Toshiaki Tsuji; Satoru Ozawa; Takuya Tamaki; et al. (PLoS ONE, 2023)
Background A primary colorectal cancer (CRC) tumor can contain heterogeneous cancer cells. As clones of cells with different properties metastasize to lymph nodes (LNs), they could show different morphologies. Cancer histologies in LNs of CRC remains to be described. Methods Our study enrolled 318 consecutive patients with CRC who underwent primary tumor resection with lymph node dissection between January 2011 and June 2016. 119 (37.4%) patients who had metastatic LNs (mLNs) were finally included in this study. Cancer histologies in LNs were classified and compared with pathologically diagnosed differentiation in the primary lesion. The association between histologies in lymph node metastasis (LNM) and prognosis in patients with CRC was investigated. Results The histologies of the cancer cells in the mLNs were classified into four types: tubular, cribriform, poorly differentiated, and mucinous. Same degree of pathologically diagnosed differentiation in the primary tumor produced various histological types in LNM. In Kaplan–Meier analysis, prognosis was worse in CRC patients with moderately differentiated adenocarcinoma who had at least some mLN also showing cribriform carcinoma than for those whose mLNs all showed tubular carcinoma. Conclusions Histology in LNM from CRC might indicate the heterogeneity and malignant phenotype of the disease.